2015
DOI: 10.1080/01587919.2015.1019964
|View full text |Cite
|
Sign up to set email alerts
|

Using TPCK as a scaffold to self-assess the novice online teaching experience

Abstract: How does one evaluate one's own online teaching? Do novice online instructors depend on end-of-semester course evaluations or a Quality Matters rubric? Perhaps their professional development is driven by a personal belief that seeking multiple perspectives from different lenses is core to reflective practice. This work explores one way to interrogate one's own online teaching practices through a systematic reflection on technological pedagogical content knowledge (TPCK). It involved identifying and reflecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Curriculum should not be recited only subject matters, but process and nature of 21 st century learners need to be designed for curriculum planning and its implementation [3,4]. Technology for education can create curriculum integration among content, pedagogy and instructional practices [5][6][7]. The learning environments are changed and seem to be differed from than previous educational management.…”
Section: Introductionmentioning
confidence: 99%
“…Curriculum should not be recited only subject matters, but process and nature of 21 st century learners need to be designed for curriculum planning and its implementation [3,4]. Technology for education can create curriculum integration among content, pedagogy and instructional practices [5][6][7]. The learning environments are changed and seem to be differed from than previous educational management.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current study also suggests that seeking students’ feedback and considering their needs were also instrumental. Furthermore, the literature and the participants also identified the importance of shared reflections and experiences with others, and close collaboration as valuable resources for instructors who seek to adapt to online teaching (Kennedy, 2015; Valsaraj et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Novice online instructors are generally defined as those who are not proficient in TPACK and lack digital literacy. For university academics accustomed to engaging in conventional face-to-face teaching, online teaching has not been a primary concern (Kennedy, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Digital Information and Communication Technologies (ICT) are present in the daily lives of a large part of the world population, especially in educational projects (ARCHAMBAULT;CRIPPEN, 2009). As part of this backdrop, research has shown that distance education, either exclusively on-line or delivered through blended learning, is part of secondary education (BORUP; GRAHAM; DRYSDALE, 2014; MIRON; GULOSINO; SHANK; DAVIDSON, 2017; MOORE-ADAMS; JONES; COHEN, 2016), tertiary education (ARINTO, 2013;DORNER;KUMAR, 2016;IGNOU, 2017;TURCSÁNYI-SZABÓ, 2012) and postgraduate degrees (HOFER; GRANDGENETT, 2012;KENNEDY, 2015).…”
Section: Distance Education and Pre-service Trainingmentioning
confidence: 99%